Introduction: Open Markets versus Welfare Citizenship: Conflicting Approaches to Policy Convergence in Europe - Taylor-Gooby, Peter (Social Policy & Administration, 2003)
Few would have predicted the rapid progress of the EU in developing common economic institutions 20 or 30 years ago, although many commentators might have foreseen the relatively slow development of convergent social policies. This paper sets the European debate in the context of the path-breaking work of Polanyi and Schumpeter at the end of the Second World War. It argues that the economic institutions of the EU are at least as important as the social policy institutions in understanding current developments, and suggests that a commitment to a broadly liberal market agenda at the economic level constrains and moulds social policies.
Keywords: European Union; SCHUMPETER, Joseph Alois, 1883-1950; economic institutions; market; social policy; welfare state

The future of planning at the 'end of history' - Goonewardena, Kanishka (Planning Theory, 2003)
The hegemony of neoliberalism now poses a fundamental challenge to planners worldwide. Most influential in this regard has been Francis Fukuyama's 'end of history' ideology and its progenies - or mutations - such as the Third Way. A close reading of their proponents (especially Anthony Giddens) and critics (Perry Anderson, Pierre Bourdieu, Alex Callinicos, John Gray and others) with reference to the contrasting political-economic theories of Friedrich von Hayek and Karl Polanyi, however, reveals the fundamental contradictions of neoliberalism - especially between capitalism and democracy - and identifies for progressive planning the role of extending radical democracy to the realms of the state and the economy.
Keywords: BOURDIEU, Pierre, 1930-2002; FUKUYAMA, Francis; GIDDENS, Anthony; HABERMAS, Jurgen; neoliberalism; planning; social democracy

Beyond Social Democracy? Takis Fotopoulos' Vision of an Inclusive Democracy as a New Liberatory Project - Gare, Arran (Democracy & Nature: The International Journal of Inclusive Democracy, 2003)
Towards an Inclusive Democracy, it is argued, offers a powerful new interpretation of the history and destructive dynamics of the market and provides an inspiring new vision of the future in place of both neo-liberalism and existing forms of socialism. It is shown how this work synthesizes and develops Karl Polanyi's characterization of the relationship between society and the market and Cornelius Castoriadis' philosophy of autonomy. A central component of Fotopoulos' argument is that social democracy can provide no answer to neo-liberalism, so the only viable alternative to neo-liberalism is the form of inclusive democracy he elaborates. Reviewing Castoriadis' concept of autonomy, it is argued that while Fotopoulos is certainly correct given the present deformed nature of social democracy, there is no reason to exclude social democracy as such from what Fotopoulos calls the tradition of autonomy. It is suggested that if the working class movement could free itself from the capitalist imaginary and return to its quest for autonomy, a synthesis or a radically reformed social democracy and inclusive democracy could greatly improve the prospects of each to successfully challenge not only neo-liberalism, but also the emerging liberal fascism of USA, Britain and Australia.
Keywords: FOTOPOULOS, Takis; autonomy (political science); democracy; liberalism; political science; socialism

Global Transformation and Local Countermovements: The Prospects for Democracy Under Neoliberalism - Udayagiri, Mridula; Walton, John (International Journal of Comparative Sociology (Sage Publications, Ltd.), 2003)
This article compares Mexico and India's experiences with neoliberalism to propose that the collapse of the development state generates countermovements. In both nations, neoliberalism is associated with the decline of the one-party deminant system, and a restructuring of civil society. Variations emerge in the timing of democratization in these countries. In India, democratization preceded neoliberal reforms, whereas in Mexico democratization followed neoliberal reforms, but in both cases democratization mitigates the effects of neoliberalism on civil society. Conclusions drawn from the comparative analysis of Mexico and India concur with Karl Polanyi's proposition that there is a double movement of marketization and protectionest countermovements. The case studies suggest a pattern to these countermovements. Actors are confronted abruptly with threats to their well-being; not only economic threats but also environmental, political , and symbolic threats. The threatened value in each case is a former entitlement, typically a form of protection ensured by the state. Thus, even in the presence of countermovements, neoliberalism mediates a divergence of state and civil society relationships creating uncertain futures for democratic possibilities.
Keywords: India; International Monetary Fund; Mexico; democracy; democratization; liberalism

The Great Transformation II: Human Rights Leapfrogging in the Era of Globalization - Howard-Hassmann, Rhoda (Conference Papers -- American Political Science Association, 2003)
Whether globalization will result in improvement or deterioration in protection of human rights is not a matter that can be observed in the short term. Globalization is, in effect, the second ‘great transformation’ (Polanyi) spreading capitalism over the entire world. In consequence, many of its short-term effects will be negative. Nevertheless, its medium and long-term effects may well be positive, as it impels social changes that will result in greater moves to democracy, economic redistribution, the rule of law, and promotion of civil and political rights. Capitalism is a necessary, though hardly sufficient condition for democracy: democracy is the best, though not the inevitable, political system to protect human rights. This does not mean that the non-Western world will follow the exact same path to protection of human rights that the Western world followed. The West had a singular advantage: it was not expected to protect human rights during its own era of economic expansion. Thus, the West was able to practice slavery, expel surplus populations, and colonize other parts of the world. Genocide and ethnic cleaning were permissible state activities. The non-Western world does not enjoy the advantage of human rights lawlessness. It does, however, enjoy other advantages occasioned by the presence of human rights. There is a global communications network and a global pro-human rights social movement. There is also the movement to global governance. Finally, and paradoxically, there is the global social movement against globalization, which forces some reflection upon its deleterious consequences. Thus, the non-Western world benefits from geographical and chronological human rights ‘leapfrogging’. This, along with the social changes that global capitalism and industrialism may impel, may mean that the medium and long-term consequences of globalization are positive for human rights.
Keywords: capitalism; democracy; globalization; human rights; human rights advocacy; social change

The World-Historical Origins of Pan-Islamic Nationalism in Iran - Araghi, Farshad (Conference Papers -- American Sociological Association, 2003)
In examining the world-historical context of the rise of pan-Islamic nationalism in Iran, this paper posits Islamic fundamentalism as a modern and global (rather than premodern and local) movement. Drawing on Polanyi and linking economy, polity, and culture, this study traces the origins of pan-Islamic nationalism in Iran to the transformation of the world-market relations in the second half of the nineteenth century and the rise of the food/agrarian regime after 1870. It shows that the relations of the state and the mercantile classes with the world market led to conflicting developments, viz., the national "contraction" of the state on the one hand and the international "expansion" of commercial classes on the other hand. The latter, in the course of their struggles for state representation, merged with the rising pan-Islamic reaction against European expansion in the "Islamic world." Pan-Islamism, by its capacity for articulating the economic nationalism of the mercantile classes in ethical terms, mobilized the masses of people for the struggle for the nationalization of the state. Hence, as a historical form, modernity and nationalism in the late nineteenth century Iran took a nonsecular character. Later, the Cold War politics revivified the pan-Islamic component of Iranian nationalism, creating the context for the rise to power of fundamentalism in the 1980s. The paper warns against the reification of place and culture rooted in binary conceptualizations of the local and the global phenomena.
Keywords: Iran; Islam; Islamic fundamentalism; culture; fundamentalism; market; nationalism; pan-Islamism; protestant fundamentalism; religion; religious fundamentalism; world; world-market relations

Labor Organizing and Neoliberal Politics - Rudy, Preston (Conference Papers -- American Sociological Association, 2003)
Neo-liberal policies and practices which impugn state policies as artificial interferences in the smooth operation of markets are at work globally, nationally and locally. Based on research about the Justice for Janitors in California, this paper examines the experience of the campaigns in San Jose and Sacramento. The paper is organized around a tension between two issues about markets that are explained by Karl Polanyi: their social reality as complex political constructions and the ideological justification for disembedding markets, aka the "Liberal Creed". In both campaigns the Justice for Janitors exposed the embeddedness of employers. On the other hand, in the ideological construction of their campaigns, the Justice for Janitors have not clearly confronted the "liberal creed" that justifies neo-liberal market practices. The JfJ campaigns have been successful at creating accountability for employers and politicians by revealing the concrete social relations within which markets are embedded, though they have largely failed to articulate an oppositional ideology to the liberal creed. At a minimum confronting this creed would place the state as central to the construction of market practices. The successes at instituting accountability of employers to democratic communities and the centrality of the state in securing that accountability will be undermined unless JfJ exposes the flaws of the liberal creed and clearly explains the importance of the state in securing the justice they seek.
Keywords: United States; ideology; labor; labour; liberal creed; liberalism; markets; neoliberalism; political planning

Debt Peonage in Granada, Nicaragua, 1870-1930: Labor in a Noncapitalist Transition - Dore, Elizabeth (Hispanic American Historical Review, 2003)
Revisits the debt peonage debate, central to understanding Latin American transitions to capitalism, particularly in Diormo, Granada, Nicaragua. Differences between capitalist and noncapitalist societies according to Karl Polanyi and Robert Brenner; Land peasantry in Diriomo; Legislation enacted to compel peasants to work in plantation agriculture.
Keywords: BRENNER, Robert, 1943-; Nicaragua; capitalism; debates and debating; history; labor laws & legislation; labour laws & legislation; peasants

Reinstituting the Economic Process: (Re)embedding the Economy in Society and Nature - Adaman, Fikret; Devine, Pat; Ozkaynak, Begum (International Review of Sociology, 2003)
Polanyi argued that the project of creating a fully self-regulating market was utopian, in the sense of impossible. However, movement towards this utopia, the ever greater but never completed process of disembedding the economy from both society and nature, creates growing dislocations and tensions which call forth a counter movement. This double movement may be thought of as successive changes in the way in which the economic process is instituted. The focus of the paper is on the meaning of embeddedness, the ways in which the economy was reinstituted during the Great Transformation and the subsequent counter movements, and alternative approaches to further reinstituting the economy in ways that disembed it further or (re)embed it more firmly in society and nature. It is argued that prior to the creation of the capitalist market the economy was organically embedded in society and nature. However, the creation of separate economic institutions, the institution of the economic process as a distinct system with its own laws of motion, severed these organic links and the economy came to dominate both society and nature. Here, however, the symmetry between society and nature ends. Society has the capacity for conscious, purposeful action; nature does not. For the economy to be reinstituted in ways that create a sustainable organic relationship with nature, it must first be reinstituted in ways that bring it under social control.
Keywords: CAPITALISM; POLANYI, Karl, 1886-1964; SOCIAL control; UTOPIAS; capitalism; economic development; economic policy; embeddedness; nature; social control; utopias

The Forgotten Institution - Cangiani, Michele (International Review of Sociology, 2003)
Presents views of scholar Karl Polanyi on economic integration. Views of Polanyi on modern capitalist society; Distinction between external, local and internal markets by Polanyi. The three forms of economic integration include reciprocity, redistribution, and exchange. The article discusses Polyani's book "The Great Transformation," the development of market economies, the self-regulating market, some of the writings of Max Weber, big businesses, the efficiency of the market system, and social engineering.
Keywords: Great Transformation, The (Book); WEBER, Max, 1864-1920; big business; capitalism; international economic integration; social engineering

Institutions, Politics and Culture: a Polanyian Perspective on Economic Change - Harriss, John (International Review of Sociology, 2003)
Presents the perspective of philosopher Karl Polanyi on economic change. Works of Polanyi on the topic; Analysis of pre-modern economies by Polanyi. According to Jeffrey Nugent, institutions make social life fairly predictable by restricting some actions and providing incentives for other actions. The article discusses Polanyi's book "The Great Transformation," the self-regulating market economy, scarcity, individual choice, economic development in India, trust in India's corporate sector, new institutional economics, and distribution of private property rights.
Keywords: Great Transformation, The (Book); India; NUGENT, Jeffrey; economic development; institutional economics; personal property; philosophers; scarcity; social interaction

The Enforcement of Contracts and Property Rights: Constitutive versus Epiphenomenal Conceptions of Law - Hodgson, Geoffrey M. (International Review of Sociology, 2003)
Discusses various conceptions of law. Concept of law as an epiphenomenon of underlying structures; Views of economist Karl Marx on law. Discusses doctrine of individualism, constitutive role of law, property rights, contracts, the emergence of law, social ontology, the relations of individuals with social structures, self-organizing institutions, self-enforcement, Karl Polyani's view that self-regulating markets are unattainable, rule of law, social reality, and how the nature of legal relations affects socio-economic behavior.
Keywords: MARX, Karl, 1818-1883; economists; individualism; law; personal property; rule of law; social reality; social structure; socioeconomics

Moral Philosophy and Economic Sociology: What MacIntyre Learnt from Polanyi - McMylor, Peter (International Review of Sociology, 2003)
Focuses on the issue of moral philosophy and economic sociology. Views of philosopher Alasdair MacIntyre on morality; Works on morality. Discusses morality in social science, Karl Polyani's writings on the social context of economic change, Marxist socialism, human cooperation, social relations, self-interest, moral responsibility, market order, public ownership, redistributive taxation, social welfare, Max Weber's ethic of responsibility, and the connections between MacIntyre's and Polyani's thoughts on morality.
Keywords: MACINTYRE, Alasdair C.; Marxian economics; WEBER, Max, 1864-1920; ethics; moral and ethical aspects; philosophers; responsibility; social psychology; social sciences; socioeconomics; sociology

The Creation of the European Market for Mobile Telephony: Overview of an Instituted Process - Mina, Andrea (International Review of Sociology, 2003)
Focuses on the creation of the European market for mobile telephony. Merits of the global system for mobile communications; Reasons for the emergence for a market for mobile telephony. Discusses the socio-economic factors that influenced the development of the mobile telephony market, the writings of Karl Polyani, instituted process, the process of standardization, digital technology, European telecommunications during the 1980s, and the development of market structure in the global equipment industry.
Keywords: Europe; global system for mobile communications; industrial organization (economic theory); instituted economic process; instituted process; mobile communication systems; standardization; telecommunication

Polanyian Perspectives on Instituted Economic Processes, Development and Transformation: Introduction - Ramlogan, Ronnie; Harvey, Mark (International Review of Sociology, 2003)
Focuses on the presentation 'Polanyian Perspectives on Instituted Economic Processes, Development and Transformation' at an international workshop held at Manchester, Connecticut. Organizer of the workshop; Theme of the workshop. The workshop was organized by the Centre for Research on Innovation and Competition. The article discusses varieties of capitalism, supply and demand, price formation, competition, economic motives, market economy, and the book "The Great Transformation," by Karl Polyani.
Keywords: Connecticut; Great Transformation, The (Book); Manchester Conn.; POLANYI, Karl, 1886-1964; United States; capitalism; competition; supply and demand; workshops (adult education)

Issues for a Neo-Polanyian Research Agenda in Economic Sociology - Randles, Sally (International Review of Sociology, 2003)
Kari Polanyi Levitt has commented that her father's writing was met with a 'deafening silence' in England, a silence which she suggests is 'yet to be explained'. Given The Great Transformation was purposefully, situated in England Polanyi Levitt's point is an interesting one, and one which still deserves attention. But the last two decades have witnessed an intensification of interest in Karl Polanyi's methodological approach and theoretical insights, from England as well as elsewhere, and representing a range of disciplines. This raises a string of associated questions: interest from who? Why now? And how? Further we could ask: Does this new interest have the potential to redress the Polanyi Levitt charge without falling prey to an opposite one of misusing or abusing the Polanyi legacy? This paper contributes to the much larger agenda of examining in a serious way the usefulness and applicability of Polanyi's key ideas and methods, particularly as they apply to the burgeoning interest in markets and exchange within New Economic Sociology (NES). A sub-set of this agenda is to explore whether Polanyian insights provide a more nuanced and critical understanding of competitive processes and innovation than is currently available within Economics, Sociology or indeed Economic Sociology.
Keywords: England; Great Transformation, The (Book); POLANYI LEVITT, Kari; POLANYI, Karl, 1886-1964; Polanyi's legacy; economic sociology; economics; socioeconomics; sociology

Karl Polanyi and the writing of The Great Transformation - Block, Fred (Theory & Society, 2003)
Karl Polanyi’s 1944 book, The Great Transformation , has been recognized as central for the field of economic sociology, but it has not been subject to the same theoretical scrutiny as other classic works in the field. This is a particular problem in that there are central tensions and complexities in Polanyi’s argument. This article suggests that these tensions can be understood as a consequence of Polanyi’s changing theoretical orientation. The basic outline of the book was developed in England in the late 1930s when Polanyi was working within a specific type of Marxist framework. However, as he was writing the book, he developed several new concepts, including fictitious commodities and the embedded economy, that led in new directions. Because circumstances did not give him the time to revise his manuscript, the book is marked by a tension between these different moments in his own theoretical development. The result is that Polanyi glimpses the concept of the always embedded market economy, but he does not name it or elaborate it.
Keywords: Great Transformation, The (Book); capitalism; economics; sociology

For a Sociological Marxism: The Complementary Convergence of Antonio Gramsci and Karl Polanyi - Burawoy, Michael (Politics & Society, 2003)
Analyzes the Marxist concept of society to interpret the rise and fall of communist orders, the shift from politics of class to politics of recognition, the transition from colonialism to postcolonialism and the development of an emergent transnationalism. Relationship between sociology and Marxism; Genesis of a sociological Marxism; Theorists of society and socialism.
Keywords: GRAMSCI, Antonio, 1891-1937; administration and politics; communism and society; postcolonialism; socialism; sociology; transnationalism

The Near-Death of Liberal Capitalism: Perceptions from the Weber to the Polanyi Brothers - Roth, Guenther (Politics & Society, 2003)
Provides an overview of some critical moments in the history of liberal capitalism as perceived by some historical witnesses. Views of brothers Max and Alfred Weber on the world economy before 1914; Historical parallels to the introduction of euro bills and coins in January 2002; Access of Germany to the world market for demographic and geographic reasons.
Keywords: Euro; POLANYI, Michael, 1891-1976; WEBER, Alfred; WEBER, Max, 1864-1920; administration and politics; capitalism; economics; history of liberal capitalism

Polanyi's 'Double Movement': The Belle Époques of British and U.S. Hegemony Compared - Silver, Beverly J.; Arrighi, Giovanni (Politics & Society, 2003)
Presents a comparative analysis of the double movement of the belle époque and collapse of British hegemony with the double movement of the late 20th and early 21st century belle époque and current crisis of U.S. hegemony. Emphasis on the book 'The Great Transformation,' by Karl Polanyi; Liberal crusade for free markets in the 1830s and 1840s; Role of Great Britain as the central entrepôt of world commerce and finance.
Keywords: Great Britain; Great Transformation, The (Book); United States; administration and politics; commerce; double movement; free enterprise

Addressing the Negative Consequences of the Information Age Lessons from Karl Polanyi and the industrial revolution: A note on the politics of theorizing technology - Rogerson, Kenneth (Information, Communication & Society, 2003)
One of the great dilemmas of the information age is the tension between two dynamics: (1) the tendency of information to be free-flowing and not to lose its value as it moves and (2) the tendency to want to control that flow of information in order to profit from its value. In 1944, Karl Polanyi identified similar contradictions in the industrial revolution, except the flowing material was capital instead of information. He spent a lifetime exposing what he felt to be the negative consequences of this increasingly free-flowing capital, the hallmark of a free market economy. He advocated for a welfare state in which government intervention is necessary to control these negative effects. Given issues of the information age such as the digital divide, the commoditization of information, and security and privacy, as well as the arguments of the proponents and critics of these issues, Polanyi's concepts can provide insight into the complexities of increasingly technical and information-based societies.
Keywords: industrial revolution; information technology

Idiosyncrasy and integration: suggestions from comparative political economy - Jones, Erik (Journal of European Public Policy, 2003)
There is a growing consensus in comparative political economy that 'globalization' is not eliminating the distinctive character of specific nation-states. Even in Europe, where formal integration between countries is most profound, nation-states remain idiosyncratic. Starting from this consensus, the questions I ask are: (a) how can we explain the coincidence of national idiosyncrasy and international integration; (b) what does our explanation tell us about processes of European integration? The answers, I argue, lie in two theoretical traditions -- one stemming from Karl Polanyi's (1957) insistence on the social embeddedness of market institutions and the other from Gunnar Myrdal's (1956) interpretation of the cumulative causality behind integration at the national and international levels. Although well received in other areas, neither tradition has played much of a role in the study of the European Union. The article concludes by suggesting a research program that could develop from the interface between idiosyncrasy and integration.
Keywords: MYRDAL, Gunnar, 1898-1987; convergence (economics); embeddedness; globalization; international political economy

Democracy and the Global System: A Contribution to the Critique of Liberal Internationalism - Biancardi, F. (Palgrave Macmillan UK, 2003)
Jacket abstract: "Democracy and the Global System analyses the relationship between liberal democracy and the global system while developing a critique of liberal internationalism. Fabian Biancardi examines some of the key questions of modern politics and the major ideas of a number of significant authors and texts, including Barrington Moore Jr., Karl Polanyi, Joseph Schumpeter, Samuel Huntington and David Held. While sympathetic to the aim of spreading liberal democracy globally, he demonstrates the many tensions and contradictions involved in achieving this outcome." Google books: What are the prospects of the liberal democratic form of state spreading throughout the world? Democracy and the Global System analyses the relationship between liberal democracy and the international system while developing a critique of liberal internationalism. Fabian Biancardi examines some of the key questions of modern politics and the major ideas of a number of significant authors and texts. While sympathetic to the aim of spreading liberal democracy, he demonstrates the many tensions and contradictions involved in achieving this outcome.
Keywords: democracy; international relations; political ideologies; political science

Economic Rationality and Globalization: A Feminist Perspective - Beneria, Lourdes (Feminist Economics Today: Beyond Economic Man, 2003)
KM: a section focuses on Polanyi's analysis of the social and political construction of markets and of "market society" in Europe, and then discusses the extent to which this type of analysis can be applied to the formation of global markets in the late twentieth century. It then looks at gender dimensions and the tension between the assumptions of economic rationality associated with market behaviour and the real-life experiences of women and men. Beneria then extends this analysis to the effects on women of globalization and the feminization of the labour force.
Keywords: feminism; feminization of labour force; gender; globalization; market society

Social Capital, Karl Polanyi, and American Social and Institutional Economics - Carroll, Michael C.; Stanfield, James Ronald (Journal of Economic Issues, 2003)
Keywords: World Bank; communities; division of labor; evolutionary economics; institutional economics; market economies; market economy; social capital; social networks; socioeconomics; solidarity

The Life and Work of Karl Polanyi/Karl Polanyi in Vienna: The Contemporary Significance of The Great Transformation - Dimand, Robert (Review of Radical Political Economics, 2003)
This article reviews two books about the thoughts of economist Karl Polanyi including "The Life and Work of Karl Polanyi," edited by Kari Polanyi-Levitt, and "Karl Polanyi in Vienna: The Contemporary Significance of the Great Transformation," edited by Kenneth McRobbie and Polanyi-Levitt.
Keywords: Karl Polanyi in Vienna: The Contemporary Significance of The Great Transformation (Book); Life and Work of Karl Polanyi, The (Book); MCROBBIE, Kenneth; POLANYI LEVITT, Kari; book review; economics; nonfiction

War and Social Change in Modern Europe: The Great Transformation Revisited - Halperin, Sandra (2003)
Halperin traces the persistence of traditional class structures during the development of industrial capitalism in Europe, and the way in which these structures shaped states and state behavior and generated conflict. She documents European conflicts between 1789 and 1914, including small and medium scale conflicts often ignored by researchers and links these conflicts to structures characteristic of industrial capitalist development in Europe before 1945. This book revisits the historical terrain of Karl Polanyi's The Great Transformation (1944), however, it argues that Polanyi's analysis is, in important ways, inaccurate and misleading. Ultimately, the book shows how and why the conflicts both culminated in the world wars and brought about a 'great transformation' in Europe. Its account of this period challenges not only Polanyi's analysis, but a variety of influential perspectives on nationalism, development, conflict, international systems change, and globalization.
Keywords: Great Transformation, The (Book); capitalism; class; critique; nationalism